Uji Hedonisme Sediaan Gel Antijerawat Dari Jeruk Nipis - diah ratnasari; Riskha Aulia; Anindi Lupita Nasyanka (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2021)
Clean, smooth, and disease-free facial skin is a dream. However, the reality is that many people have skin problems. The skin problem that often occurs is acne. One way to treat acne is by using herbal preparations. Herbal plants that have anti-acne properties include Citrus aurantiifolia and menthol. The purpose of this study was to make antiacne gel preparations from Citrus aurantiifolia and menthol. There are also stages of this research, including formula making, production and physical evaluation of preparations to obtain the best dosage formulas. In addition, the determination of the optimum stability and formula is obtained from the physical evaluation of the gel preparation which includes organoleptic and hedonism test. Keyword : herbal, Citrus aurantiifolia, menthol, hedonism test